Whole-exome sequencing in fetuses with central nervous system abnormalities. (October 2018) - Reches, Adi; Hiersch, Liran; Simchoni, Sharon; Barel, Dalit; Greenberg, Rotem; Ben Sira, Liat; Malinger, Gustavo; Yaron, Yuval
Abstract Objective We describe our experience with whole-exome sequencing (WES) in fetuses with central nervous system (CNS) abnormalities following a normal chromosomal microarray result. Methods During the study period (2014–2017) 7 cases (9 fetuses) with prenatally diagnosed CNS abnormality, whose chromosomal microarray analysis was negative, were offered whole-exome sequencing analysis. Results A pathogenic or a likely pathogenic variant was found in 5 cases including a previously described, likely pathogenic de novoTUBA1A variant (Case #1); a previously described homozygousVRK1 variant (Case #2); an X-linkedARX variant (Case #3); a likely pathogenic heterozygous variant in theTUBB3 gene (Case #5). Finally, in two fetuses of the same couple (Case #6), a compound heterozygous state was detected, consisting of theNPHP1 gene deletion and a sequence variant of uncertain significance. Two additional cases had normal WES results. Conclusion Whole-exome sequencing may improve prenatal diagnosis in fetuses with CNS abnormalities.